SARS-CoV-2 infection in nonhuman primates alters the composition and functional activity of the gut microbiota. (1st January 2021) - Sokol, Harry; Contreras, Vanessa; Maisonnasse, Pauline; Desmons, Aurore; Delache, Benoit; Sencio, Valentin; Machelart, Arnaud; Brisebarre, Angela; Humbert, Lydie; Deryuter, Lucie; Gauliard, Emilie; Heumel, Severine; et al.
ABSTRACT: The current pandemic of coronavirus disease (COVID) 2019 constitutes a global public health issue. Regarding the emerging importance of the gut-lung axis in viral respiratory infections, analysis of the gut microbiota's composition and functional activity during a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection might be instrumental in understanding and controling COVID 19. We used a nonhuman primate model (the macaque), that recapitulates mild COVID-19 symptoms, to analyze the effects of a SARS-CoV-2 infection on dynamic changes of the gut microbiota. 16S rRNA gene profiling and analysis of β diversity indicated significant changes in the composition of the gut microbiota with a peak at 10–13 days post-infection (dpi). Analysis of bacterial abundance correlation networks confirmed disruption of the bacterial community at 10–13 dpi. Some alterations in microbiota persisted after the resolution of the infection until day 26. Some changes in the relative bacterial taxon abundance associated with infectious parameters. Interestingly, the relative abundance of Acinetobacter (Proteobacteria) and some genera of the Ruminococcaceae family (Firmicutes) was positively correlated with the presence of SARS-CoV-2 in the upper respiratory tract. Targeted quantitative metabolomics indicated a drop in short-chain fatty acids (SCFAs) and changes in several bile acids and tryptophan metabolites in infected animals. The relative abundance of several taxa known to be SCFA producers (mostly from the Ruminococcaceae family) was negatively correlated with systemic inflammatory markers while the opposite correlation was seen with several members of the genus Streptococcus . Collectively, SARS-CoV-2 infection in a nonhuman primate is associated with changes in the gut microbiota's composition and functional activity.